CO and CO2 methanation over M (M[dbnd]Mn, Ce, Zr, Mg, K, Zn, or V)-promoted Ni/Al@Al2O3 catalysts - Le, Thien An; Kim, Jieun; Kang, Jong Kyu; Park, Eun Duck (Catalysis Today, 2020)
Effects of metal promoter on CO and CO2 methanation were examined over Ni-M (M = Mn, Ce, Zr, Mg, K, Zn, or V)/Al@Al2O3 catalysts prepared by the co-impregnation method. Ni-M (M = Mn, Ce, or Zr)/γ-Al2O3 catalysts were also investigated for comparison. The prepared catalysts were characterized with a variety of techniques such as N2 physisorption, CO2 chemisorption, H2 chemisorption, temperature-programmed reduction with H2 (H2-TPR), temperature-programmed desorption of CO2 (CO2-TPD), X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and in-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). Among different promoters, Mn, Ce, Mg, V, and Zr are beneficial to enhance both CO and CO2 methanation activity due to the improvement of the Ni dispersion. The Ni-V/Al@Al2O3 catalyst performs the highest CO methanation activity due to the largest Ni sites. However, it is not the best one for CO2 methanation among tested catalysts because of the much decrease in CO2 adsorption capacity. The promotional effect of Mn is the most remarkable for both CO and CO2 methanation. On the other hand, the negative effect of K and Zn was observed on both CO and CO2 methanation by the small number of active Ni sites and the decrease in the amount of basic sites. The CO2 methanation mechanism over Ni-Mn/Al@Al2O3 catalyst is elucidated by the transform route: adsorbed carbonate species – formate species – methane under hydrogenation process.
Keywords: Carbonate species; Co methanation; Hydrogenation process; N2 physisorption; Promoter; Promotional effect; Situ diffuse reflectance infrared Fourier transform spectroscopy; Temperature-programmed reduction; Al@Al2O3; Ce; CO methanation; CO2 methanation; Mn; Ni; Promoter; γ-Al2O3